Bemerkungen zu Manetho und zur manethonischen Tradition: I. Die dritte Dynastie - Theis, Christoffer (Die Welt des Orients, 2014)
The present study discusses the written record of the third Egyptian dynasty of Sextus Julius Africanus in the tradition of Manetho with special reference to the names of the kings and their sequence. By comparison of the Greek denominations with the known Egyptian kings, it is shown that Manetho, Africanus or a third unknown writer mixed up this dynasty in parts with the fourth dynasty and mentions Snofru, Cheops, Chephren and Mykerinos as rulers. The tradition of the third dynasty is based at least on two different sources, which is clear from comparison with the Egyptian names known from kinglists of the New Kingdom and consideration of their Greek equivalents. In conclusion, it seems to be that the source of Manetho holds only three rulers; the nine kings, to whom Africanus refers, are in main part doublets and kings of the fourth dynasty.